PERAN PEMAHAMAN GOOD CORPORATE GOVERNANCE DALAM MEMEDIASI PENGARUH BUDAYA ORGANISASI DAN PERILAKU ETIS TERHADAP KINERJA PEGAWAI BANK BPD BALI - Anak Agung Istri Diah Jayanti; Rahayu Puji Suci; Nasharuddin Mas (Jurnal Cakrawala Ilmiah, 2024)
This research aims to empirically analyze the role of understanding good corporate governance in mediating the influence of organizational culture and ethical behavior on the performance of Bank BPD Bali employees. A quantitative approach is used as a research method based on the philosophy of positivism. The population in this study was all employees, totaling 1,374 employees. The sampling technique used was probability sampling with the technique taken, namely proportionate stratified random sampling with a total of 93 employees as respondents. The data analysis technique used in this research is Partial Least Square-Structural Equation Modeling (PLS-SEM) using smartPLS version 4 software. The research results show that organizational culture is unable to improve employee performance. Organizational culture is able to increase understanding of good corporate governance. Ethical behavior is unable to improve employee performance. Ethical behavior is able to increase understanding of good corporate governance. Understanding good corporate governance can improve employee performance. Understanding good corporate governance plays a role in mediating organizational culture in improving employee performance. Understanding good corporate governance plays a role in mediating ethical behavior in improving employee performance/